2014 not found: a cross-platform approach to retrospective web archiving. Issue 3 (2nd October 2019) - Ben-David, Anat
Abstract: While web archiving techniques capture snapshots of websites in real time, this article introduces an approach for building special collections for web archiving in retrospect. Retrospective web archiving (RWA) aims to fill-in gaps in existing archives, as well as to expand the boundaries of web archiving from the open web to cross-platform curation, and from national to international perspectives. The proposed approach is tested on a case study of the 2014 War in Gaza. The retrospective collection contains 118, 508 unique URIs and relevant metadata, carbon-dated to the period of the military operation, in 46 languages and 5692 domain suffixes, collected from Wikipedia, Google, Twitter and YouTube. Findings suggest that four years after the war, 50% of the URIs were still available on the live web, but only 38% of them have already been archived elsewhere. Although URL sharing on social media was found the most relevant for retrospective curation, the platformisation of the web, along with the popularity of URL shortening services, severely impacts their archival coverage. The article suggests taking into account platform dynamics and cultural differences in link sharing practices, when thinking about future curation policies for both real time and RWA.